INDUCTION ENDOSPORE FORMATION OF Bacillus subtilis KM16 AS A PROBIOTIC CANDIDATE BY OPTIMIZATION OF THE GROWTH CONDITIONS - Stella Magdalena; Adelaide Geraldine; Yogiara (LPPM Universitas PGRI Semarang, 2024)
Probiotics are living microorganisms which have beneficial effects. One of the benefits is enhancing immunity. Therefore, probiotics are often supplemented into food, medical, and aquaculture products. B. subtilis KM16 as endospore-producing bacteria have been known to increase probiotic resistance to confront the unstable conditions of the digestive tract. Spore formation of Bacillus is supported by the optimal condition of growth medium and incubation periods. The sufficient availability of carbon, nitrogen, and mineral source in the growth medium, and environmental conditions can support the formation of optimal endospores. This research aimed to determine the suitable sugar composition of a medium and optimum incubation time suitable for endospores formation of B. subtilis KM16. Glucose and maltose were utilized as a carbon source in several concentration as a growth medium for B. subtilis KM 16. The incubation time was 48 and 72 hours. The viable number of vegetative cells was not significantly different for the type of sugar and incubation periods. Based on the glucose concentration, 0.2% glucose exhibited the uppermost number of cells, while 1% glucose concentration caused the decrease of vegetative cells. In this study, 0.2% glucose with 48 hours incubation period showed the highest percentage of sporulation frequencies, up to 48%, but it was not significantly different from the other glucose concentration. The medium that contains 0.2% glucose with 48 hours incubation period is the best medium for the utilization of B. subtilis KM16 cells and spores as probiotic candidates.